Cynical consumer: how social cynicism impacts consumer attitude. Issue 1 (9th December 2020) - Indibara, Indirah; Varshney, Sanjeev
Abstract : Purpose: This paper aims to examine the effect of social cynicism on consumer cynicism. The negative inferred motive is tested as a mediator between social cynicism and consumer cynicism; whereas, negative affectivity is tested as a moderator between social cynicism and negative inferred motive. Design/methodology/approach: The study was carried out in India using a mixed-method approach. In the first stage, a survey was conducted to test the moderated mediation model, followed by in-depth interviews in the second stage. The survey was analysed using structural equation modelling, while themes were generated from the data collected through interviews. Findings: The study established the effect of social cynicism on consumer cynicism. Negative inferred motive mediated the relationship between social cynicism and consumer cynicism. Negative affectivity moderated the influence of social cynicism on negative inferred motive. Research limitations/implications: With rising anti-consumption behaviours, it is imperative to understand why consumers turn cynical towards marketers. The study indicates that consumer cynicism is influenced by previous experiences of the consumer with the society and is not merely a reaction to arm-twisting by firms. As social cynicism cannot be changed drastically, understanding how it impacts consumer cynicism would help a firm handle its marketing efforts better. Originality/value: The study empirically validates the relationship between social cynicism and consumer cynicism. The mediating effect of negative inferred motive on consumer cynicism was also validated. The study is also the first to point out the moderating role of negative affectivity on the relationship between social cynicism and negative inferred motive.